PENGEMBANGAN MULTIMEDIA PEMBELAJARAN SD PADA MATERI SIFAT-SIFAT MAGNET DALAM KEHDUPAN SEHARI-HARI TEMA 5 KELAS VI - Diah Putri, Tiara; Setiawati, Tiya; Agung Juwantara, Ridho (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
This study aims to develop the use of multimedia as a learning medium for elementary school students, with this multimedia students will find it easier to understand the material taught by the teacher and also the teacher will more easily explain the material to students because there is an animated video as an intermediary. This research is a research and development or Research and Development (R&D). Borg and Gall. The result of this research is a class 6 learning video with 5 themes about the properties of magnets in everyday life. The conclusion of this study is that it is important for teachers to develop multimedia as a support for learning so that students are able to understand the material properly and correctly so as to improve the results of students' cognitive and applications in everyday life. With this multimedia, students can also carry out the maximum learning process.